Measurement of electroweak-induced production of W gamma with two jets in pp collisions at root s=8TeV and constraints on anomalous quartic gauge couplings - (:unkn) unknown (SPRINGER, 2017)
A measurement of electroweak-induced production of W gamma and two jets is performed, where the W boson decays leptonically. The data used in the analysis correspond to an integrated luminosity of 19.7 fb(-1) collected by the CMS experiment in root s = 8TeV proton-proton collisions produced at the LHC. Candidate events are selected with exactly one muon or electron, missing transverse momentum, one photon, and two jets with large rapidity separation. An excess over the hypothesis of the standard model without electroweak production of W gamma with two jets is observed with a signi fi cance of 2.7 standard deviations. The cross section measured in the fi ducial region is 10.8 +/- 4.1(stat) +/- 3.4(syst) +/- 0. 3(lumi) fb, which is consistent with the standard model electroweak prediction. The total cross section for W gamma in association with two jets in the same fi ducial region is measured to be 23.2 +/- 4.3(stat) +/- 1.7(syst) +/- 0.6(lumi) fb, which is consistent with the standard model prediction from the combination of electroweakand quantum chromodynamics-induced processes. No deviations are observed from the standard model predictions and experimental limits on anomalous quartic gauge couplings integral M,0- 7 /Lambda(4), integral T,0- 2 /Lambda(4), and integral T,5-7/Lambda(4) are set at 95% con fi dence level.
Keywords: Electroweak interaction; Hadron-Hadron scattering (experiments); proton-proton scattering